Pembangunan sistem pencalonan anugerah perkhidmatan cemerlang (SPAPC) menggunakan kaedah Proses Analitik Berhierarki (PHA) - Hanan, Binti Mohd Bidin. (unimas, 2017)
Performance appraisal is a significant and effective management to ensure and control the employee's performance that have been highlight in an organization objectives .The purpose of this study is to develop a system that can support the decision making process that when the problems is involving a multi-criteria in order to achieve a goal Regarding to these research related to performance appraisal techniques ,Analytical Hierarchy Process (A HP ) is chosen to be applied in developing on system management information in the organization .Phase Development Based methodology is used as methodology in developing the system. For implementation phase ,the programming language that have been applied is Visual Basic Application coding and .mdb in Microsoft Access IS used as the database for the system. Hopeful this system will be beneficial and can Support to overcome the problem. The system will be develop with a simple interfaces and useful function to assist the user with simple function with the current technology.